Analysis of Science Process Skills Improved From Student Activities Through Inquiry Training Learning Model - Siregar, Halimatus Sadyah; Mihardi, Satria (Universitas Negeri Medan, 2020)
Science skills are skills that students need when they are investigating. These skills are needed by students in the process of inquiry to solve problems from a natural phenomenon that is around them. general reality many of the skills of students who tend to be passive and low. The low scientific skills of students because the learning process does not involve practicum. Therefore, this study aims to find out. Improved science skills in terms of high school student activities through inquiry training learning models. This type of research is descriptive. The instrument of this study was the activity evaluation observation sheet. Each student observation sheet consists of five indicators. The indicator is confronting the problem, verifying data, experimenting, processing data and inquiry analysis. The results showed that skills based on assessment of activity indicators increased at each meeting.